DEMOKRASI DAN MULTI KULTURALISME DALAM KONTESTASI DAKWAH ISLAM - Rusdin Ahmad (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
The essence of democracy is justice and equality in all aspects of life, including rights as the individual, citizen, and the God’s creatures. The plurality of God’s creatures is a part of natural law, which is called multiculturalism. Cultural pluralism is not separated from democracy. Democracy is a system of state which is regulated constitutionally and legitimizes all interests and rights of the individuals.